Improving Parental Investments in Children: Experimental Evidence from The Gambia - Moussa Blimpo; Pedro Carneiro; Pamela Jervis Ortiz; Nathalie Lahire; Todd Pugatch (Institute of Labor Economics (IZA), 2024)
We study two early childhood programs in The Gambia for children between 0 and 3 years of age. The basic version of the program, called Baby Friendly Community Initiative (BFCI), provides parents with child health and nutrition information delivered through home visits and community meetings. A second version, called BFCI+, is center-based and adds cognitive stimulation to the basic version of the program through activities with children. Villages were randomly assigned to one of two versions of the program or to a control group that received neither. The BFCI+ program had moderate impacts on parental investments in children in terms of resources and time. Child language development improved for well-off parents or parents in the more well-off region. Poorer parents invested more in time spent with the children, whereas those who were more materially well-off spent more financial resources on the children. The basic version of the program, the BFCI, had no detectable impacts.
Keywords: I25; I38; O15; O22; 330; early childhood development; cognitive stimulation; teacher training; The Gambia; randomized controlled trials; Malawi Developmental Assessment Tool